Petro Rents and Higher Education: A Cross-country Examination - Javadi, Shahin; Motevaseli, Mahmood; Farsi, Jahangir Yadolahi (International Journal of Economics and Financial Issues, 2017)
This study provides an empirical investigation to test one of the transmission channels of resource curse, i.e. higher education. Our panel data analysis of 70 countries from 2006 to 2014 shows petro rents have a positive impact on the indicator of higher education and training in developed countries but petro rents have no statistically significant effect on the indicator of higher education and training in developing countries. We also find petro rents have a positive impact on the quality of education in both groups of countries but we find a negative and statistically significant association between petro rents and the quantity of higher education in developing countries which can explain resource curse. These findings are robust when we control for other major drivers of dependent variables, unobservable country- and time-fixed effects. Keywords: resource curse, oil rents, higher education, human capital JEL Classifications: I25; O15; O13